Contribution to the knowledge of cave-dwelling fauna from the Prokletije Mountains - Kocot-Zalewska, Joanna; Słowińska, Iwona; Domagała, Paweł; Bienias, Jakub; Szymański, Dominik; Szymański, Dawid; Szymański, Hubert; Sienkiewicz, Paweł; Woźnica, Andrzej Józef (International journal of speleology, 2025)
The article presents the results of the study on invertebrate fauna inhabiting caves in the Prokletije Mountains. This mountain range is located on the border of Montenegro, Albania, and Kosovo. During the expeditions to Albania in 2021 and to Montenegro in 2022–2023, 17 caves and one bauxite mine were visited altogether. All the studied caves are located very high, above 1,700 m a.s.l., where the temperature inside is low, and several are filled with ice or snow. During the Albanian expedition 102 arthropods have been collected altogether. Among these were 19 beetles (Coleoptera), 44 flies (Diptera), three crickets (Orthoptera), five millipedes (Diplopoda), 16 Opiliones, six spiders (Araneae), two springtails (Collembola), and one tick (Ixodida). During the Montenegrin expeditions 226 specimens belonging to ten groups have been collected: 119 flies (Diptera), 32 beetles (Coleoptera), 20 caddisflies (Trichoptera), 21 spiders (Araneae), 20 Opiliones, six millipedes (Diplopoda), four bristletails (Archeognatha), two crickets (Orthoptera), one pseudoscorpion (Pseudoscorpionida), and one isopod (Isopoda). Ten species we recognized as troglobionts, four as eutroglophiles, and 11 as subtroglophiles. Among the collected species, three are new to Albanian fauna and two to Montenegrin fauna.